Agile Human Resources: Harnessing Agility To Drive Organizational Success - Waruwu, Eliyunus (Universitas Muhammadiyah Tapanuli Selatan, 2024)
The purpose of this research is to determine the extent to which the implementation of Agile HR in companies can be effectively applied, as well as to identify the factors influencing the implementation of Agile HR in this company. This study employs a qualitative descriptive approach through literature review, focusing solely on explaining and elucidating the implementation of Agile HR in the company and the factors influencing it. While some studies utilize quantitative descriptive methods, this research solely delineates the implementation of Agile HR and its influencing factors in detail without employing statistical data. The research methodology utilized in this article is a descriptive approach coupled with literature analysis. Agile HR offers an adaptive and responsive approach to addressing the rapidly changing business landscape and has proven to be effective in optimizing organizational performance. It brings significant benefits to organizations, including enhanced flexibility, speed, and adaptability. By adopting Agile principles within the Human Resources function, organizations can improve their efficiency, flexibility, adaptability, and achieve long-term success amidst increasingly fierce global competition. The success of Agile HR also involves other key factors. In performance management, Agile HR offers a more adaptive approach focused on continuous feedback. Skill development and training are also crucial focuses within Agile HR. Additionally, fostering a culture and work environment that supports collaboration and innovation are key aspects of Agile HR.